HUBUNGAN PERILAKU PICKY EATING DENGAN STATUS GIZI PADA SISWA SDIT BUNAYYA MEDAN - Emi Inayah Sari Siregar; Abdul Hairuddin Angkat (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Introduction: Picky eating is a condition in which children are picky about food or only consume certain foods. Picky eating occurs due to a lack of variety in the foods that are introduced to children. If this lasts a relatively long time, it can result in a lack of energy and other nutrients. Purpose : to determine the relationship between picky eating behavior and nutritional status of SDIT Bunayya Medan students. Design : analytic observational using a cross sectional study approach. The population is all students in class IV SDIT Bunayya Medan consisting of 2 classes and a total of 60 people. Sampling in total sampling. Results : The most dominant non picky eating behavior was 51,66% and picky eating was 48,33%. Most of the respondents had normal nutritional status of 53,33% and undernourished 46,66%. Based on the statistical test results, the p-value was 0.002 <? (0.05). Conclusion: There is a significant relationship between picky eating behavior and nutritional status of SDIT Bunayya Medan students.